Micro cone beam computed tomography for sensitive assessment of radiation-induced late lung toxicity in preclinical models. (September 2019) - van Berlo, D.; Khmelinskii, A.; Gasparini, A.; Salguero, F.J.; Floot, B.; de Wit, N.; van de Ven, M.; Song, J.Y.; Coppes, R.P.; Verheij, M.; Sonke, J.J.; Vens, C.
Highlights: μIGRT of full right lungs of mice with heart sparing is feasible. μCBCT determined lung densities increase in a dose‐dependent manner. Lung function is affected in a dose‐dependent manner. μCBCT allows the sensitive detection of effects inflicted by small dose increments. Aggravation of radiation‐induced lung damage by cisplatin as detected by μCBCT. Abstract: Background and purpose: Preclinical models are much needed to assess the effect of novel radio-sensitizers or mitigators on radiation dose limiting lung toxicity. Albeit showing radiation-induced lung pathologies, current mouse models lack the sensitivity to do so. Using micro image-guided radiotherapy (µIGRT) techniques, we aimed to establish murine models which enable the sensitive detection of lung damage aggravation and characterized functional, radiological and histological responses. Materials and methods: Right lungs of C57Bl/6J mice were irradiated using µIGRT with doses from 15 to 27 Gy and with 21 Gy and cisplatin as a radio-sensitizer in a second study. Mice were sacrificed for histological and pathological assessment at different time-points post-IR. Lung density was determined using the integrated micro cone-beam CT (µCBCT). Lung function was measured by double-chamber-plethysmography. Results: µIGRT resulted in accurate deposition of the radiation dose in the right lung only as determined by ɣH2AX staining. Lung fibrosis was confirmed by pathological assessments and increased significantly at 21 Gy as determined by automated quantification of histochemical analyses. Lung function was affected in a dose-dependent manner. µCBCT-determined lung densities increased significantly over time in the irradiated lungs and showed a strong radiation dose-dependence. Importantly, the µCBCT analyses allowed the detection of additional lung damage caused by 3 Gy dose increments or by the combination with cisplatin. Conclusion: µCBCT after right lung µIGRT enables the sensitive detection of effects inflicted by relative small dose increments or radio-sensitizers. Our preclinical model therefore facilitates the determination of lung damage exacerbation for the safety assessment of novel RT-drug combinations.